PERUBUHAN PERUNTUKAN KAWASAN HUTAN MENJADI BUKAN KAWASAN HUTAN UNTUK MENAJAMIN HAK MASYARAKAT ATAS TANAH - Dede Frastien (University Of Bengkulu Law Journal, 2017)
Forest area damage continues to occur due to various factors including weak control and supervision of the operation of the licensing system in the management of forest areas, conversion of functions, conversion of forest areas to plantations, settlements and / or other non-forestry interests (Mining). the expected results of this paper are knowing and understanding related to the mechanism of implementing the Land Object of Agrarian Reform in Forest Areas based on Government Regulation Number 88 of 2017 and inhibiting factors in the application of Land Objects for Agrarian Reform in Forest Areas based on Presidential Regulation Number 88 of 2017. This paper is writing normative law using the case approach method. The results obtained, namely, comprehensive socialization regarding the mechanism regulated in LHK Ministerial Regulation Number 83 of 2016 concerning Social Forestry must be sought. Through the schemes offered by LHK Minister Regulation No. 83 of 2016 concerning Social Forestry, the community can contribute greatly and partner in maintaining the preservation and protection of forest areas and improving the economy. Concerns about the implementation of Presidential Regulation No. 88 of 2017 are the inclusion of extractive industry interests and the loss of managed areas of the people which have been maintained for generations.